Aptamer-Hytac Chimeras for Targeted Degradation of SARS-CoV-2 Spike-1 - Carme Fàbrega; Núria Gallisà-Suñé; Alice Zuin; Juan Sebastián Ruíz; Bernat Coll-Martínez; Gemma Fabriàs; Ramon Eritja; Bernat Crosas (Cells, 2024)
The development of novel tools to tackle viral processes has become a central focus in global health, during the COVID-19 pandemic. The spike protein is currently one of the main SARS-CoV-2 targets, owing to its key roles in infectivity and virion formation. In this context, exploring innovative strategies to block the activity of essential factors of SARS-CoV-2, such as spike proteins, will strengthen the capacity to respond to current and future threats. In the present work, we developed and tested novel bispecific molecules that encompass: (i) oligonucleotide aptamers S901 and S702, which bind to the spike protein through its S1 domain, and (ii) hydrophobic tags, such as adamantane and tert-butyl-carbamate-based ligands. Hydrophobic tags have the capacity to trigger the degradation of targets recruited in the context of a proteolytic chimera by activating quality control pathways. We observed that S901-adamantyl conjugates promote the degradation of the S1 spike domain, stably expressed in human cells by genomic insertion. These results highlight the suitability of aptamers as target-recognition molecules and the robustness of protein quality control pathways triggered by hydrophobic signals, and place aptamer-Hytacs as promising tools for counteracting coronavirus progression in human cells.